Characterization and morphological evaluation of fruits in peach palm genotypes for table (Research, Society and Development, 2021)
At Embrapa Amazônia Oriental, there are peach palm (Bactris gasipaes Kunth.) from different sources conserved in the Germplasm Bank (BAG) in Tomé-Açu (PA). However, little is known about the morpho-agronomic characteristics of its fruits. The objective of the work was to characterize and evaluate fruits of genotypes of this palm conserved in the BAG aiming to identify plants with promising characteristics for table fruits. 100 peach palm representing of 50 accessions were studied, from which samples were collected from 15 ripe fruits of each plant, which were evaluated and characterized, morphologically, by ten quantitative and six qualitative characters. The data were subjected to univariate and multivariate analyzes (grouping) to define the most homogeneous groups. Then, there was a concatenation between the groups formed by the quantitative and qualitative characters. There was a divergence among the evaluated genotypes, making it possible to form five distinct groups based on quantitative characters and eight groups related to qualitative characters. The joint character analysis allowed the identification of 45 genotypes with promising characteristics for the table market.